A Successful Treatment of Locally Advanced Breast Cancer with Using Mohs' Paste and Chemotherapy - A Case Report - Tsubota, Yu; Yamamoto, Daigo; Ishizuka, Mariko; Yoshikawa, Katsuhiro; Sueoka, Noriko; Kon, Masanori (Gan to kagaku ryoho, 2018)
Foul smell and large amounts ofexudate, bleeding are the most common and serious symptoms with locally advanced breast cancer(LABC). Mohs' paste is made ofa mixture ofzinc chloride and used for treatment ofmalignant skin tumors. Recently some reports show that Mohs' paste is useful for treatment of malignant tumor including unresectable breast cancer and skin metastasis ofcancer. Mohs' paste is useful for reducing symptoms such as foul smell and exudate, Bleeding. We report a successful case of treatment for LABC with using Mohs' paste and chemotherapy and surgery.